INFLUENCE OF HEME VINYL-PROTEIN AND CARBOXYLATE PROTEIN CONTACTS ON STRUCTURE AND REDOX PROPERTIES OF BOVINE CYTOCHROME-B5 - LEE, KB; JUN, ES; LAMAR, GN; REZZANO, IN; PANDEY, RK; SMITH, KM; WALKER, FA; BUTTLAIRE, DH (AMER CHEMICAL SOC, 1991)
H-1 NMR spectroscopy and optical spectroelectrochemistry on a thin-layer electrode have been utilized to investigate the influence of heme vinyl- and carboxylate-protein contacts on heme pocket structure and reduction potential of bovine ferricytochrome b5. In spite of the diverse modifications of heme vinyls and carboxylates, H-1 NMR results indicate that there are no significant perturbations in the heme orientation and essential electronic structure. This allows us to attribute changes in redox properties to the role of each vinyl- or carboxylate-protein contact in cytochrome b5. While pemptohemin (2-H, 4-vinyl) and isopemptohemin (2-vinyl, 4-H) exhibit essentially identical reduction potentials outside the protein in DMF solution, protein reconstituted with pemptohemin shows an E0 (ca. -8 mV vs SHE) closer to that of native protein (2-vinyl, 4-vinyl; ca. -2 mV), and protein substituted with isopemptohemin exhibits an E0 (ca. -38 mV) closer to that of deuterohemin (2-H, 4-H; ca. -52 mV). Hence the 4-vinyl group accounts for the dominant electron-withdrawing influence on the porphyrin skeleton of the native protein, with the 2-vinyl group providing a minor effect. These results are consistent with the NMR data which indicate a sterically clamped, largely in-plane (maximal electron withdrawing) 4-vinyl group and a 2-vinyl group that is mobile and largely out of plane (minimal electron withdrawing). The reduction potentials for the cytochrome b5 complex of 2,4-dimethyldeuterohemin and heptamethyl monopropionate hemin, with the lone propionate of the latter hemin making the protein link as for the 7-propionate of the native protein, are ca. -83 and ca. -58 mV, respectively. Moreover, the reduction potentials vary insignificantly when the pair of carboxylate side chains are both lengthened or shortened by one carbon. Therefore, the influence on reduction potential for the 7-propionate in the native protein is not substantially larger than that for the 6-propionate, and argues against this uniquely oriented 7-propionate of native cytochrome b5 providing an important stabilizing interaction for oxidized cytochrome b5.
Keywords: PHOTOSYNTHETIC BACTERIAL CYTOCHROMES-C2; PROTON MAGNETIC-RESONANCE; PORPHYRIN COMPLEXES; ELECTRON-TRANSFER; REDUCTION; FERRICYTOCHROME-B5; ORIENTATION; RESOLUTION; B5; EQUILIBRIUM